Asuhan Keperawatan Jiwa pada Ny. I Dengan Masalah Utama Gangguan Sensori Persepsi : Halusinasi Pendengaran Akibat Skizofrenia Paronoid di Ruang Arimbi RSJD Dr. Amino Gondohutomo Provinsi Jawa Tengah - Firnanda Mutiara Herlita; Titi Sri Suryanti; Tati Karyawati (Jurnal Mahasiswa Ilmu Kesehatan, 2024)
Mental health is a condition of mental, physical and emotional health where individuals have positive things in terms of self-actualization, perception according to reality and skills in adapting to the environment. Schizophrenia is a form of long-term mental disorder with communication disorders and blunted affect that affects the individual's normal daily activities with hallucinations (Puspitasari & Astuti, 2024). The purpose of writing this work is to find out and implement nursing care for Mrs. I with the main problem of sensory perception disorders, auditory hallucinations due to paranoid schizophrenia in the Arimbi Room, RSJD dr. Amino Gondohutomo, Central Java Province. The preparation method uses a descriptive approach with case studies as a writing plan. The case review obtained was that the main problem was that Mrs. I heard a man's voice saying bad things and often seemed to be talking to herself. The nursing problem tree shows sensory perception disorders: auditory hallucinations as the core problem, then self-care deficits, social isolation and risk of violent behavior. Interventions are structured based on implementation strategy guidelines aimed at clients and families which will later be implemented and evaluated immediately as documentary evidence.